Global change and energy markets: Analysis the effects of Nordic electricity market integration on environmental policy using GTAP-E model - Juha Forsström; Juha Honkatukia; Pekka Sulamaa (The Research Institute of the Finnish Economy (ETLA), 2003)
This study applies the GTAP-E model which incorporates carbon emissions from the combustion of fossil fuels and this provides for a mechanism to trade these emissions internationally. This facilitates an analysis of North European Energy production and energy markets while still consistently taking into account the effects of global trade and global abatement. We analyse the effects of energy market integration on the scope of national abatement policies in the countries on the Baltic Rim, and especially in Finland. Energy markets will influence emissions policies via technological opportunities for energy production and for energy trading. The costs of abatement will also depend on the degree of competitiveness of energy markets. Also the effects of the use of Kyoto mechanisms on competitiveness and efficiency in the North European markets are analysed. Energy market integration will itself depend on global and European abatement targets. The main finding of the study is that while emission trading clearly may lead to more cost-efficient and less costly abatement, the integration of energy markets can by itself lead to cost reductions of almost the same magnitude. Also, while the emission permit price is lower due to the electricity market integration there are both losers and winners within the Nordic group. – – Tässä tutkimuksessa hyödynnetään globaalia numeerisesti laskettavaa yleisen tasapainon mallia (GTAP-E), jossa on myös mukana CO2 päästöt. Mallissa CO2 päästöt syntyvät hiilen, öljyn ja liikennepolttoaineiden käytöstä tuotannossa tai loppukulutuksessa. Tutkimuksessa analysoidaan sekä Kioton sopimuksen mukaista että pelkän EU:n kattavan päästökaupan ja Pohjoismaiden sähkömarkkinoiden integroitumisen vuorovaikutuksia. Energiamarkkinoiden vapautuminen kilpailulle ja niiden osittainen integroituminen vaikuttaa päästökaupan kustannuksiin mm. fossiilisten polttoaineiden helpomman korvattavuuden kautta. Tutkimustulosten mukaan sähkömarkkinoiden integroituminen saattaa tuoda merkittäviä kustannussäästöjä hiilidioksidipäästöjen vähentämisessä, joskin Pohjoismaiden sisällä vaikutukset eivät ole kaikille aina suotuisat johtuen mm. vaihtosuhteiden muuttumisesta.
Keywords: 330; Globalisierung; Energiemarkt; Umweltpolitik; Allgemeines Gleichgewicht; Dänemark; Finnland; Schweden; Norwegen